Keupayaan pendekatan institusi dalam menghurai punca-punca tanah pertanian terbiar di daerah Kuala Pilah, Negeri Sembilan - Azima Abdul Manaf, (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2007)
This research examined the explanatory power of institutional perspectives with regard to the causes of and solutions for idle agriculture land in Kuala Pilah, Negeri Sembilan. There are several causes of agriculture idle land that can be classified into formal written and informal unwritten sources. According to the institutional perspective, formal institutions affect actors’ behaviour. Therefore, a study on formal institutions enables us to identify the way in which actors are willing to supply land for agriculture development. Similarly, informal rules or the attitudes of the actors also affect supply of land in the case study area. Data was collected through interviews with landowners and government officers to identify the written and unwritten rules that caused idle lands using nonstratified sampling procedure and involving 52 lots of idle lands within 19 villages in Kuala Pilah District. This study adopted the qualitative method of analysis with emphasis on landowners’ behaviour. The findings showed that one of the major causes of land becoming idle was due to the social relations of the agents. The findings therefore indicated the importance of formal dan informal rules in the supply of land for agriculture development in the case study areas